Prevalence of neutralising antibodies to Berne virus in animals and humans in Vellore, South India - Brown, D. W. G. (Arch Virol, 1988)
In Southern India the prevalence of neutralising antibody to Berne virus was high in sera obtained from cattle (49%), horses (38%), and sheep (36%). Neutralising antibody was not detected in sera from humans and monkeys.